x-11=2(-7)
x=11-14
x=-3
Check:
-1/7 (-3-11)=(-1/7)(-14)=2 OK
Or did you mean
-1/(7(x-11))=2 Then
-1=14(x-11)
x=11 - 1/14
x=10 13/14
Check:
-1/(7/-1/14))=14/7=2 OK
2006-11-25 08:52:23
·
answer #1
·
answered by albert 5
·
0⤊
0⤋
Yes, you would multiply by the reciprocal first.
-1/7(X-11)=2 ----------The original problem
-7[-1/7(X-11)]=2(-7)-------- Multiply both sides by the reciprocal (-7)
X-11=-14 ------ The problem after multiplied by -7
(X-11)+11=(-14)+11 ------- Add 11 to each side to get x by itself
X=-3 ------- the answer!
2006-11-25 17:04:16
·
answer #2
·
answered by Glitterz23 2
·
0⤊
0⤋
ok it's -1/7x+ (watever 1/7 times 11 is) =2.... then you subtract the answer to 1/7 x 11 and add it to the other side... then you divide that answer by - 1/7... hope that helps
2006-11-25 16:51:28
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Sure, why not? It makes things easier
Since you eventually want to isolate x, you can push the - to the other side too by multipling by -7:
x-11 = -14
x = -3, right?
2006-11-25 16:53:07
·
answer #4
·
answered by modulo_function 7
·
0⤊
0⤋
ok, first multiply (x-11) by -1/7
so its
-1/7 times x
and
-1/7 times -11
then solve for x by substracting/adding.
2006-11-25 16:52:58
·
answer #5
·
answered by olivemenow 2
·
0⤊
0⤋
-7 * -1/7 (x-11) = -7*2
x-11 = -14
x = -3
2006-11-25 16:54:05
·
answer #6
·
answered by Jim Burnell 6
·
0⤊
0⤋